2012
DOI: 10.1177/0960327112438929
|View full text |Cite
|
Sign up to set email alerts
|

Dietary flaxseed oil supplementation ameliorates the effect of cisplatin on brush border membrane enzymes and antioxidant system in rat intestine

Abstract: Cisplatin (CP; cis-diamminedichloroplatinum II) is a drug widely used against different types of solid tumors. Patients receiving CP, however, experience very profound and long lasting gastrointestinal symptoms. Recently, ω-3 polyunsaturated fatty acid-enriched flaxseed/flaxseed oil (FXO) has shown numerous health benefits. The present study was undertaken to investigate whether FXO can prevent CP-induced adverse biochemical changes in the small intestine of rats. A single intraperitoneal dose of CP (6 mg/kg b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 56 publications
2
10
0
Order By: Relevance
“…tGSH keeps sulfhydryl groups of molecules reduced, inhibiting their oxidation [29]. Our finding of decreased levels of sulfhydryl groups in the jejunal tissue of animals receiving cisplatin indicates that our results are compatible with the literature [30]. In the current study, a significant decrease was found in GPO activity in the jejunal tissue of animals that received cisplatin.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…tGSH keeps sulfhydryl groups of molecules reduced, inhibiting their oxidation [29]. Our finding of decreased levels of sulfhydryl groups in the jejunal tissue of animals receiving cisplatin indicates that our results are compatible with the literature [30]. In the current study, a significant decrease was found in GPO activity in the jejunal tissue of animals that received cisplatin.…”
Section: Discussionsupporting
confidence: 92%
“…CAT is considered an enzymatic antioxidant; this substance inhibits the formation of toxic hydroxyl radicals by catalyzing the decomposition of hydrogen peroxide (H 2 O 2 ) to oxygen and water [32,33]. It has been reported that CAT activity is decreased in tissue damage induced by cisplatin [30]. Again, in our study, the levels of NO were significantly elevated in the jejunal tissue of cisplatin-administered rats.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Similar results were obtained by Rossary et al (2007), who found that SOD activity did not change when fibroblasts were treated with DHA or EPA omega-3 polyunsaturated fatty acid. On the other hand, Naqshbandi et al (2012) showed an improvement in SOD activity in the intestine from rats treated with omega-3-enriched diet. The contradictory results of SOD activity may occur due to differences between experimental protocols, mainly related to the amount of omega 3 and/or the treatment duration.…”
Section: Discussionmentioning
confidence: 95%
“…Animal studies have shown that omega-3 fatty acid may possess potent antioxidant and anti-inflammatory properties and may prevent fibrosis of different organs [ 25 ]. It also empowers the antioxidant defense system by reducing oxidative stress and increasing the activities of the major antioxidant enzymes such as superoxide dismutase, catalase, and glutathione peroxidase [ 26 ]. The American Heart Association recommends that all adults eat fish 2 to 3 times per week because of its content of ω -3FA.…”
Section: Introductionmentioning
confidence: 99%